Abu Bakar's Attitude after the Death of the Prophet Muhammad Saw: Analysis of Social Conflict from Lewis Coser's Perspective - Fikri, Maulana Muhammad; Kholil, Ahmad (Universitas Islam Negeri Sumatera Utara, 2025)
This study analyzes the role of Caliph Abu Bakr following the passing of the Prophet Muhammad Peace Be Upon Him and the response of the people of Madinah. Using Lewis Coser's social conflict approach, this research explores Abu Bakr’s actions and the social dynamics that emerged after the Prophet’s passing. Social conflict arose in the aftermath of the Prophet's death, creating tension and confusion among the people of Madinah. This qualitative descriptive study, employing Lewis Coser's social conflict approach, uses reading and note-taking techniques. Data analysis follows Miles and Huberman’s procedures, which include data reduction, presentation, and conclusion, to form a structured description. The analysis results indicate that in the context of Abu Bakr's appointment as the first Caliph after the Prophet’s passing, conflict functionalism theory provides insight into the social dynamics that took place. The conflict between the Ansar and Muhajirun played a crucial role in strengthening internal group solidarity, reinforcing group boundaries, and reducing tolerance for division. Although initial conflict arose, the deliberation and election of Abu Bakr ultimately served as a